1993
DOI: 10.1002/pd.1970131004
|View full text |Cite
|
Sign up to set email alerts
|

Serum PAPP‐A measurements in first‐trimester screening for Down syndrome

Abstract: Serum PAPP-A measurements taken from 254 women in the first trimester are reported. Eleven chromosomal abnormalities were detected. The mean serum PAPP-A levels in cases of Down syndrome were 0.44 MOM at 9 weeks gestation, 0.15 MOM at 10 weeks, and 0.29 MOM at 11 weeks. The PAPP-A level at 10 weeks was below those of pregnancies which aborted spontaneously. At 11 weeks, the pregnancies with Down syndrome recorded the lowest PAPP-A levels at that gestation. On this small sample, offering chorionic villus sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 8 publications
5
21
0
2
Order By: Relevance
“…This biochemical marker has been suggested as the single most effective in first-trimester screening [21] but, at the time of our study, this marker could not be measured by means of a reproducible automated method.…”
Section: Discussionmentioning
confidence: 74%
“…This biochemical marker has been suggested as the single most effective in first-trimester screening [21] but, at the time of our study, this marker could not be measured by means of a reproducible automated method.…”
Section: Discussionmentioning
confidence: 74%
“…PAPP-A is detectable in maternal serum by about the 30th day of pregnancy and MS-PAPP-A levels increase exponentially until term, then gradually decrease and are undetectable by the sixth postpartum week (Sinosich, 1985). MS-PAPP-A concentrations are significantly reduced in the presence of a fetus with DS, suggesting this as a sensitive marker during the first trimester (Brambati et al, 1991(Brambati et al, , 1994Cuckle and Lilford, 1992;Wald et al, 1992;Hurley et al, 1993;Bersinger et al, 1994;Macintosh et al, 1994;El Farra and Grudzinskas, 1995).…”
Section: Introductionmentioning
confidence: 87%
“…Hurley et al demonstrated that a decreased level of PAPP-A was associated with trisomy 21 and that these low levels could be detected as early as the first trimester. From these results, they concluded that using a cut off of 0.3 multiples of the median for PAPP-A, pregnancies at an increased risk for trisomy 21 could be identified (Hurley PA et al, 1993). Use of PAPP-A in conjunction with maternal age was also studied as a first trimester screening technique for trisomy 21 (Brambati B, Macintosh MC, Teisner B, Maguiness S, Schrimanker K, Lanzani A et al, 1993).…”
Section: First Trimester Screeningmentioning
confidence: 99%
“…In the early 1990s the maternal analyte PAPP-A was studied to determine its usefulness as a screening tool. These studies wanted to understand if there was a correlation between the amount of PAPP-A in maternal blood and fetal aneuploidy or demise (Hurley PA, Ward RH, Teisner B, Iles RK, Lucas M, Grudzinskas JG., 1993). Hurley et al demonstrated that a decreased level of PAPP-A was associated with trisomy 21 and that these low levels could be detected as early as the first trimester.…”
Section: First Trimester Screeningmentioning
confidence: 99%